Inflammation and dysregulated fibroblast proliferation – new mechanisms? - Kolb, M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Idiopathic pulmonary fibrosis (IPF) is a devastating, age-related lung disease of unknown cause that has few treatment options. Once thought to be a chronic inflammatory process, current evidence indicates that the fibrotic response may primarily be driven by abnormally activated alveolar epithelial cells and the underlying mesenchyme. The mediators produced and present in this microenvironment induce the formation of fibroblast foci through the proliferation of resident mesenchymal cells, attraction of circulating fibrocytes, and stimulation of epithelial to mesenchymal transition. The fibroblast and myofibroblast foci secrete excessive amounts of extracellular matrix, mainly collagens, resulting in scarring and destruction of the lung architecture. The detailed mechanisms that link IPF with ageing and aberrant epithelial activation are unknown, but some evidence suggests that the abnormal recapitulation of developmental pathways and epigenetic changes may play a role. This review provides a brief synopsis of highlights in the current understanding of the pathophysiology of IPF, as well as novel therapeutics being explored in clinical trials for the treatment of this devastating disease.